Finite Element Analysis of the Movement of the Tie-Back Wall in Alluvial-Silty Soils - Agus Setyo Muntohara, Hung-Jiun Liao (ELSEVIER, 2013)
Excavations in urban developed areas were commonly supported by diaphragm walls with internal braces or tieback anchors. There are still required the necessary civil works to serve the demands and also to solve the environmental problems. Wales and cross-lot struts are by far the predominant method for wall support, the large working space inside the excavation provided by a tieback anchor system has a significant construction advantage. This paper aims to evaluate the soil stiffness parameters of the alluvial Taipei soil for tie-back diaphragm wall based on back analysis of case study. The case histories of the Taipei County Administration Centre (TCAC) and NTU Hospital (NTUH) were studied in this paper. The deformation analysis was carried out by available finite element analysis tool using PLAXIS. In the analysis, beam element method together with an elastic perfect plastic soil model was used to design the diaphragm wall and the tieback anchor system. The soil was modelled as Mohr-Coulomb model. According to the basic design, the clay deposits are modelled as undrained behaviour while silty-sand behaves in drained condition. The simulation results show that the maximum horizontal movement occurred at around the bottom of wall. At the final stage of construction, the root mean square deviation (RSMD) between measured and calculated the wall movement was 4% and 7% respectively at TCAC and NTUH sites.